2006
DOI: 10.1186/1472-6963-6-137
|View full text |Cite
|
Sign up to set email alerts
|

Swiss residents' speciality choices – impact of gender, personality traits, career motivation and life goals

Abstract: Background: The medical specialities chosen by doctors for their careers play an important part in the development of health-care services. This study aimed to investigate the influence of gender, personality traits, career motivation and life goal aspirations on the choice of medical speciality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
113
3
21

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(159 citation statements)
references
References 27 publications
21
113
3
21
Order By: Relevance
“…Female students were more likely to choose Ob/Gyn than their their male counterparts. This result is similar to findings from Japan, Jordan, Turkey, and Switzerland (4,8,9,16). Female students were more likely to choose internal medicine and allied subjects because they involve less physical work than surgical fields like general surgery and orthopedics.…”
Section: Discussionsupporting
confidence: 80%
“…Female students were more likely to choose Ob/Gyn than their their male counterparts. This result is similar to findings from Japan, Jordan, Turkey, and Switzerland (4,8,9,16). Female students were more likely to choose internal medicine and allied subjects because they involve less physical work than surgical fields like general surgery and orthopedics.…”
Section: Discussionsupporting
confidence: 80%
“…Strong career motivation (BuddebergFisher et al 2006) or higher intrinsic career motivation (Buddeberg-Fischer et al 2003) were found to be independent predictors of choice of speciality. Students not considering any primary care specialties showed significantly higher achievement and power motives (Buddeberg-Fisher et al 2006). …”
Section: Motivation As An Independent Variablementioning
confidence: 99%
“…Career motivation and life goals (for example, intimacy, affiliation, altruism, power, achievement and variation) have been found to influence career trajectories, such as fields of specialization of Swiss medical students (Buddeberg-Fischer, Klaghofer, Abel, & Buddeberg, 2006). Currently there is limited literature discussing how goals for teaching may have either a sustaining or limiting impact on teachers' careers.…”
Section: Beyond Achievement Goalsmentioning
confidence: 99%